Arterial Destiffening Starts Early after Renal Artery Denervation. (3rd March 2019) - Berukstis, Andrius; Navickas, Rokas; Neverauskaite-Piliponiene, Gintarė; Ryliskyte, Ligita; Misiura, Jonas; Vajauskas, Donatas; Misonis, Nerijus; Laucevicius, Aleksandras
Abstract : Introduction . Renal artery denervation (RDN) is a new widely discussed method in treatment of hypertension. Most of the RDN studies assessed BP and arterial changes 3 and 6 months after the procedure, but there is a lack of trials that investigated early changes after RDN. Aim . To investigate aortic stiffness 24-48 hours after the procedure and thus to examine whether RDN might have an early additive value for a cardiovascular risk decline beyond the lowering of blood pressure. Methods . RDN was performed for 73 patients with resistant hypertension. Arterial stiffness and central haemodynamics were measured before the procedure, the next day after the procedure, and subsequently after 1, 3, 6, and 12 months. Results . Within 48 hours, RDN significantly reduced aortic pulse wave velocity (AoPWV) from 11.3±2.7 to 10.3±2.6 m/s ( p =0.001); reduction was sustained at months 1, 3, 6, and 12. Early changes in the AoPWV value did not correlate with changes in office systolic or diastolic BP ( p =0.45; p =0.33). Furthermore, the higher the initial AoPWV value, the greater the reduction of AoPWV observed after 6 months: Q1 8.4±1, Δ0.05±1.6 / Q2 10.1±0.4, Δ1.1±1.4 / Q3 12.2±0.8, Δ1.8±1.7 / Q4 15.3±1.7, Δ2.8±2.1 ( p =0.002). Conclusions . Early and sustained effects on AoPWV observed in our study suggest that RDN may have additional effects on reducing arterial stiffness and cardiovascular risk.